Anisotropic thermal expansion of Ni3Sn4, Ag3Sn, Cu3Sn, Cu6Sn5 and βSn. (December 2017) - Xian, J.W.; Zeng, G.; Belyakov, S.A.; Gu, Q.; Nogita, K.; Gourlay, C.M.
Abstract: The directional coefficient of thermal expansion (CTE) of intermetallics in electronic interconnections is a key thermophysical property that is required for microstructure-level modelling of solder joint reliability. Here, CTE ellipsoids are measured for key solder intermetallics using synchrotron x-ray diffraction (XRD). The role of the crystal structure used for refinement on the CTE shape and temperature dependence is investigated. The results are used to discuss the βSn-IMC orientation relationships (ORs) that minimise the in-plane CTE mismatch on IMC growth facets, which are measured with electron backscatter diffraction (EBSD) in solder joints on Cu and Ni substrates. The CTE mismatch in fully-intermetallic joints is discussed, and the relationship between the directional CTE of monoclinic and hexagonal polymorphs of Cu6 Sn5 is explored. Graphical abstract: Highlights: The directional CTE tensor is measured for five important phases in solders. Solder intermetallics have more isotropic CTE than βSn. IMC facets in solder joints are determined by electron backscatter diffraction. Optimum ORs to minimise in-plane CTE mismatch on facets are given.